(untitled) (Conference Zone, 2022)
The concept of virtual is widely used in the field of computer science and information technology. For example: virtual machine, virtual memory, virtual disk, virtual communication, virtual travel, virtual classroom, etc. In this field alone, the concept of virtual is used in different forms and meanings and has different meanings. For example, in multimedia systems, the concept of virtual means virtual being.